Proteins in soy might have a higher role in cancer prevention than previously expected: soybean protein fractions are more effective MMP-9 inhibitors than non-protein fractions, even in cooked seeds - Lima, Ana (2017)
The search for anticancer MMP-9 inhibitors (MMPIs) in food products has become a major goal for research. MMPIs in soy have been related only to saponins and isoflavones, but recently, low specific protein fractions in soybeans were shown to reduce MMP-9 activity as well. The present work aimed at comparing the MMPI potential of protein fractions (P) and non-protein fractions (NP) isolated from soybean seeds, before and after soaking and cooking, mimicking dietary exposures. Reverse and substrate zymography, as well as a fluoregenic DQ gelatin assay were used to evaluate MMP-9 activities. Colon cancer cell migration and proliferation was also tested in HT29 cells. Regarding MMP-9 inhibition, proteins in soy presented IC50 values 100 times lower than non-protein extracts, and remained active after cooking, suggesting that proteins may be more effective MMP-9 inhibitors than non-protein compounds. Using the determined IC50 concentrations, NP fractions were able to induce higher inhibitions of HT29 cell migration and proliferation, but not through MMP-9 inhibition, whilst protein fractions were shown to specifically inhibit MMP-9 activity. Overall, our results show that protein fractions in soybeans might have a higher role in soy-related cancer prevention as MMPIs than previously expected. Being nontoxic and active at lower concentrations, the discovery of these heat-resistant specific MMPI proteins in soy can be of significant importance for cancer preventive diets, particularly considering the increasing use of soy proteins in food products and the controversy around isoflavones amongst consumers